Applesnails of Florida Pomacea spp. (Gastropoda: Ampullariidae) - Thomas R. Fasulo (EDIS)
Applesnails are larger than most freshwater snails and can be separated from other freshwater species by their oval shell that has the umbilicus of the shell perforated or broadly open. There are four species in Florida, one of which is native and considered beneficial. Both the island and channeled applesnails are potential threats to Florida’s aquatic ecosystems. Learn more in this revised 5-page fact sheet written by Thomas R. Fasulo, and published by the UF Department of Entomology and Nematology, June 2011.